1991
DOI: 10.2166/wst.1991.0595
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Anaerobic-Aerobic Treatment of Complex Industrial Waste Water Using Biofilm Reactors

Abstract: Warm concentrated industrial wastewaters are preferably treated in an anaerobic reactor for reasons of energy generation and low surplus sludge production. Problems to be solved in the practical application concern a low growth rate of the micro-organisms, their low settling rate process instability, and the need for after-treatment of the noxious anaerobic effluent which often contains NH4+ and HS−. The use of biomass immobilized on small suspended carriers (< 0.5 mm) has proven to be a suitable mean t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

1992
1992
2001
2001

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 0 publications
2
27
0
1
Order By: Relevance
“…Most of the modern, high-capacity wastewater treatment systems, such as the upflow anaerobic sludge bed (UASB), airlift reactor, and fluidized-bed and internal circulation reactors (Peereboom and Vereijken, 1994), make use of suspended bioparticles. Small suspended carriers are used as substrata for biofilm formation in airlift and fluidized-bed reactors (Heijnen et al, 1991;Wagner and Hempel, 1988) and to provide an intermediate stage in aggregate formation, for example in anaerobic gas-lift (Beeftink and Staugaard, 1986) and UASB reactors (Lettinga, 1995). They have also been used to control excessive biofilm formation in such systems (Wagner and Hempel, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the modern, high-capacity wastewater treatment systems, such as the upflow anaerobic sludge bed (UASB), airlift reactor, and fluidized-bed and internal circulation reactors (Peereboom and Vereijken, 1994), make use of suspended bioparticles. Small suspended carriers are used as substrata for biofilm formation in airlift and fluidized-bed reactors (Heijnen et al, 1991;Wagner and Hempel, 1988) and to provide an intermediate stage in aggregate formation, for example in anaerobic gas-lift (Beeftink and Staugaard, 1986) and UASB reactors (Lettinga, 1995). They have also been used to control excessive biofilm formation in such systems (Wagner and Hempel, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…In developed countries, much progress has been made in monitoring and controlling emissions from these sources. However, much remains to be done in many developing countries from both technological and economic points of view (Nair, 1990;Heijnen et al, 1991;Li and Chu, 1991;Wong, 1997). Somlyody (1995) addressed the issues of water-quality management through point source control.…”
Section: Point Sourcesmentioning
confidence: 99%
“…As to technologies for point source control, Heijnen et al (1991) proposed a large-scale biofilm reactor system for treating industrial wastewater through a combined anaerobicaerobic process. Cooke (1994) studied the mechanism of nutrient transformation in a natural wetland that is used for receiving sewage effluent.…”
Section: Point Sourcesmentioning
confidence: 99%
“…Bode [ 4 ] found that the effluent qualities achieved for pectin, sugar, and animal pulp industrial wastewaters subjected to solely aerobic treatment were better than those from sequential anaerobiclaerobic treatment. Heijnen et al [5] studied a full scale three stage sequenced anaerobidaerobic process for the treatment of an industrial waste containing COD, kjeldahl nitrogen, and sulfate. All three units employed immobilized biomass to reduce process size, The first two units were for anaerobic pretreatment and were followed by an aerobic unit primarily for ammonium and sulfide oxidation.…”
Section: Previous Experience With Sequenced Anaerobwaerobic Treatmentmentioning
confidence: 99%